A closer look at the species behind abundance–occupancy relationships. (7th June 2013) - Eriksson, Ove
Abstract Guedo & Lamb (2013), in this issue of the Journal of Vegetation Science, used a 35‐yr data series from two prairie communities to show that abundance–occupancy relationships change over time. Scrutinizing the details behind this finding, they show that species groups follow different trajectories during succession after disturbance. These results will inspire further species‐level studies unraveling mechanisms behind abundance–occupancy relationships.